2016
DOI: 10.1161/circulationaha.115.019692
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Angiopoietin-2 Level in Patients With Continuous-Flow Left Ventricular Assist Devices Leads to Altered Angiogenesis and Is Associated With Higher Nonsurgical Bleeding

Abstract: Background Non-surgical bleeding (NSB) is the most common adverse event in patients with continuous-flow left ventricular assist devices (LVADs) and is caused by arteriovenous malformations (AVMs). We hypothesized that deregulation of an angiogenic factor, Angiopoietin-2 (Ang-2), in LVAD patients leads to increased angiogenesis and higher NSB. Methods Ang-2 and thrombin levels were measured by ELISA and Western blotting, respectively, in blood samples from 101 patients with heart failure (HF), LVAD, or ortho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
93
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 133 publications
(99 citation statements)
references
References 55 publications
6
93
0
Order By: Relevance
“…Inclusions, exclusions and timing of recruitment were reported previously 12 and are addressed in the Supplementary Material (available online at www.jhltonline.org/). The protocol was approved by the institutional review board of the University of Chicago and all participants provided written informed consent.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Inclusions, exclusions and timing of recruitment were reported previously 12 and are addressed in the Supplementary Material (available online at www.jhltonline.org/). The protocol was approved by the institutional review board of the University of Chicago and all participants provided written informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…8,9 Ang-2 induces endothelial destabilization and altered vessel growth. 10,11 We have shown that Ang-1 is decreased in LVAD patients, 12 although the underlying mechanism is unknown. We have also shown that thrombin-dependent overexpression of Ang-2 in LVAD patients induces altered angiogenesis and is associated with NSB.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9 We demonstrated recently that thrombin-induced angiopoietin-2 expression in LVAD patients leads to increased angiogenesis in vitro which may contribute to AVM formation in vivo . 10 …”
Section: Introductionmentioning
confidence: 99%
“…It is thought that the loss of pulsatility and potential hypoxia result in upregulation of angiogenic mediators, such as vascular endothelial growth factor and angiopoietin-2, may contribute to the development of angiodysplasia. [10][11][12] Consequently, appropriate primary and secondary bleeding prophylaxis is essential in improving long-term outcomes after LVAD implantation.…”
mentioning
confidence: 99%